2012
DOI: 10.1055/s-0032-1317012
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Methods to Access Chiral Camphanyl Amine Derivatives by ­Sodium Borohydride Reduction of d-(–)-Camphorquinone Imines

Abstract: D-(-)-Camphorquinone imines prepared using methanolic ammonia, ethanol amine, exo-(-)-bornylamine, ethylene diamine, propylene diamine, and trans-(R,R)-1,2-diaminocyclohexane, upon reduction using sodium borohydride in methanol, give the corresponding chiral exo amino alcohol and diamine derivatives in good yields (75-95%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…7 Also, the chiral camphorylpiperazine derivatives were prepared by condensation of ethylenediamine with optically active camphorquinone. 8 A similar condensation process with 1,2 diaminocyclohexane was also reported. 9 Herein, we report methods for synthesis of piperazine derivatives containing chiral bi-2-napthyl moiety.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…7 Also, the chiral camphorylpiperazine derivatives were prepared by condensation of ethylenediamine with optically active camphorquinone. 8 A similar condensation process with 1,2 diaminocyclohexane was also reported. 9 Herein, we report methods for synthesis of piperazine derivatives containing chiral bi-2-napthyl moiety.…”
supporting
confidence: 55%
“…Subsequent condensation of this keto ester (R)-3 with ethylenediamine (4) in anhydrous methanol gave the product (R)-5 in 90% yield. We have observed that similar condensation reactions of (R)-3 with 1,2-diaminobenzene (6) and (2R,3R)-1,2-diaminocyclohexane (8) under reflux conditions furnished cyclic products (R)-7 and (R)-9 in 90% and 88% yield, respectively.…”
mentioning
confidence: 89%
“…Because the generated mine would be hydrolysed in the presence of water, the anhydrous methanol/DMSO mixed solvents were used as the reaction medium in the reaction between melamine and glutaraldehyde. Besides, in order to enhance the stability of the melamine modified layer, NaBH 4 was adopted as the reductant to convert the unstable imine bond into stabilized amine .…”
Section: Resultsmentioning
confidence: 99%
“…Chiral piperazine derivative 4 containing a camphanyl moiety was readily prepared by a recently reported method (Scheme ) 7…”
Section: Resultsmentioning
confidence: 99%